Impact of Family Conflict on the Psychosocial Behaviour in Male Adolescents - Chhabra, GS; Sodhi, MK (Journal of Nepal Paediatric Society, 2012)
Introduction: Accepting and supportive family relationships during childhood and adolescence may have long-term associations with psychosocial functioning into adulthood. Cross-sectional studies provide evidence by which positive family relationships promote adolescent health by increasing the likelihood of positive outcomes including higher educational and occupational attainment and reducing the risk for negative outcomes including suicidal behaviour and poor health. Materials and Methods: The sample consisted of 500 male adolescents from the urban and rural field practice areas in the vicinity of Sri Guru Ram Das Medical College Amritsar. Cross sectional study was conducted to examine the relation between familial conflict problems and psychosocial/behavioural disorders in adolescents. Results: Almost one third (33%) adolescents were having parental and family dispute problems. These problems were significantly higher in middle adolescence (14-16 years), adolescents of large extended families (>8 members) and in lower socioeconomic status. Residence had no significant relation to family problems in the adolescents. On correlation, poor and unhealthy family atmosphere had more chances in adolescents of having greater academic problems, depression, suicidal thoughts, substance abuse and more sexual activity. Conclusion: Family involvement, family structure, parental values, parental monitoring and parent-child communication are important factors influencing critical life choices in teens. The family support and communication should be improved through these education programs to develop healthy psychosocial and sexual attitudes and counteract unsafe behaviours in the adolescents. Future research is needed to identify additional pathways underlying this association, and the extent to which these factors are modifiable. J. Nepal Paediatr. Soc. 32(2) 2012 124-131 doi: http://dx.doi.org/10.3126/jnps.v32i2.6147